Hubungan Pengetahuan Tentang Kekerasan Dalam Pacaran Terhadap Sikap Remaja Putri Di Kabupaten Tabanan - Tammimin Ummah; Indah Purnamasari; Eka Vicky Yulivantina (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Backgroud : Violence still a problem in reproductive health, one of which is violence in dating. Violence in dating is found, but many teenagers still don't know, so sometimes they don't realize that they are victims of violence in dating. The worldwide dating violence rate is estimated at 200,000 or 43% of dating violence between 10-29 year olds. Studi Methouds : The research design used descriptive quantitative research with a cross sectional design. The population of this study were high school students at the Bali Bina Insani Islamic Boarding School, Tabanan Regency totaling 42 people. The sampling technique in this research is the total sampling technique. Univariate data analysis with frequency distribution table, bivariate analysis with square test. Results : Characteristics of respondents based on age, most of the respondents were 14 young women aged 17 years (33%), the characteristics of respondents based on class were mostly 15 teenage girls in grades X and XII (36%), characteristics of respondents based on the age of first dating mostly at the age of 15 years as many as 8 young women (36%) and 19 young women (45%) have never been in a relationship, the knowledge of young women about violence in dating is mostly good knowledge as much as 18 (43%), the attitudes of young women about violence in dating are mostly quite as many as 30 (71%), and there is a relationship between knowledge about violence in dating on the attitudes of young women in Tabanan district with a square test with an P value of 0.000 <0.05. Conclusion : There is a relationship between knowledge about violence in dating and the attitude of young women at SMA Bali Bina Insani, Tabanan Regency